The Influence of Perceived Price Fairness, Product Quality and Service Quality on Customer Loyalty mediated by Customer Satisfaction at XYZ Furniture Manufacturer in Surabaya - Aprianto, Dwi Wahyu; Sukoco, Badri Munir (International Journal of Science and Society, 2024)
The war between Ukraine and Russia caused disruption in the furniture export process. To overcome this problem, PT. BMN as a company operating in the furniture industry carries out a strategy to maintain the company's business processes by increasing customer loyalty. The goal is to analyze the impact of Perceived Price Fairness, Product Quality and Service Quality on Customer Satisfaction and Customer Loyalty. Quantitative causal type research by collecting data through questionnaires which was analyzed by SEM PLS. Population study is the key person in purchasing furniture. The sample was determined using purposive sampling so that the total sample was 41 respondents. The study prove that Perceived Price Fairness and Product Quality do not have a significant impact on Customer Satisfaction, while Service Quality has a significant impact. Perceived Price Fairness, Product Quality, Service Quality and Customer Satisfaction have a significant impact on Customer Loyalty.